Knowledge Discovery: Preprocessing Technique in Web Server Data log - - Supriyadi (INKOM Journal, 2017)
Preprocessing is a process to avail a clean and ready data for data mining analysis. Four stages are carried out in this process i.e. data selecting, data cleaning, data integrating and data transforming. The numerous semi structured pattern of web server log data accumulation has made the data cleaning-up to select the really needed data difficult. Hence, in this research a technique to carry out data cleaning using parser algorithm and query processing is proposed. The parser algorithm is written using PHP programming as web based programming, while the query processing is implemented using relationship database management system (RDBMS) MySQL. The computation system is tested using twenty six different sized trial data, originated from six web server. The final result concluded that in general the data being tested have 80 percent decreasing average with average processing velocity of 9.28 mbpsKeywords: query processing, parser algorithm, semi structured data, web log data